Application of Think Pair Share Learning Model and Video to Improve Students’ Writing Skill - Marwa Yasmine Zaidi; Nashruddin Nashruddin (JELITA, 2021)
The aims of the current research are to describe (1) the improvement of students’ writing persuasive paragraph skill; (2) the improvement of students’ learning attitudes after taking persuasive paragraph writing lessons with the Think Pair Share model and educational videos; (3) the increase of students’ learning motivation after taking persuasive paragraph writing lessons with the Think Pair Share model and educational videos. This is a quantitative and qualitative research, with the number of participants are 30 students from high school in Kairouan city. The instruments used to collect data were observation, questionnaires, interviews, and documentation. Based on the results of research that had been done, it was known that students’ skills in writing persuasive paragraphs had increased. It was known from the results of writing persuasive paragraphs in each cycle. In the pre-cycle, the average score of the students was 43.5. In the 1st cycle, the average score of students increased to 61.17. In the 2nd cycle, students got an average score of 64.83. In the 3rd cycle, the average score of students were 78.00. This proves that the results of writing persuasive paragraphs of students have increased in cycle I, cycle II, and cycle III.